(untitled) (Latakia University Journal -Biological Sciences Series, 2016)
Fish farming using earthen ponds is considered one of the most commonly-used ways in Syria. It is one of the important resources of fish production in the country .In the last years ,the importance of producing fish to meet the needs of Syrian citizensfor animal protein has increased ,due to the shortage of sources and the increasing prices of animal products on one hand , and the greatly growing population on the other. The research aims to achieve the following objectives: 1 -Calculating the Production costs for all production processes contained in stages farming fish in ponds and carry out a study and analysis of these costs account. 2- The economic evaluation t of farming fish using earthen ponds in Latakia through the expense of some economic analysis indicators. Through research we came to the following results: 1-The net profit achieved was102847,3 SYP/1000m2 2- The total production costs was147952,7SYP/1000m2 3-The farm Production efficiency reached 1,97and the economic efficiency 1.69 4-The profitability index as related to production costs amounted to 81.83 % and as related to the invested capital amounted to 20.65%. تعد تربية الأسماك بطريقة الأحواض الترابية من الطرق الواسعة الانتشار في سورية , والتي تشكل مصدراً مهماً من مصادر الإنتاج السمكي في القطر , وفي السنوات الأخيرة ازدادت أهمية الإنتاج السمكي، لتأمين حاجة المواطن من البروتين الحيواني في ظل محدودية الموارد، وارتفاع أسعار المنتجات الحيوانية الأخرى من جهة , والتزايد السكاني الكبير من جهة ثانية . هدف البحث إلى تحقيق الأهداف الآتية : 1- حساب التكاليف الإنتاجية لكافة العمليات الإنتاجية التي تتضمنها مراحل تربية الأسماك في الأحواض الترابية، ودراستها، وتحليلها . 2- التقييم الاقتصادي لتربية الأسماك بالأحواض الترابية في محافظة اللاذقية من خلال حساب بعض مؤشرات التحليل الاقتصادي. من خلال البحث توصلنا إلى النتائج الآتية : - بلغ صافي الربح المحقق 102847,3 ل.س للدونم الواحد. - بلغت التكاليف الإنتاجية الإجمالية 147952,7 ل.س للدونم الواحد. - بلغت الكفاءة الإنتاجية المزرعية 1,97، و الكفاءة الاقتصادية 1,69. - بلغ معامل الربحية بالقياس إلى التكاليف الإنتاجية 81,83% ، و بالقياس إلى رأس المال المستثمر 20,65% .